Judicial dispute resolution (JDR) : new roles for judges in ensuring justice / Lawrence Susskind, William Tilleman, and Nicolas Parra Herrera. - Susskind, Lawrence; Tilleman, William Arthur, II, 1955-; Parra Herrera, Nicolás (Anthem Press, 2023)
This book describes the ways in which judges, using JDR, have been facilitating problem-solving among litigants, and in the process, ensuring more just outcomes. JDR or judicial dispute resolution is similar to mediation (or alternative dispute resolution - ADR, as it is sometimes called), but it is provided by a judge, not a private mediator. Very little has been written about JDR, especially in Canada where it has been pioneered for several decades, because all the records have remained confidential. The story can now be told because the authors were given exclusive access to the records and the parties (including the JDR judges) in nine illustrative cases. The authors provide a complete Teaching Appendix summarizing the JDR cases from the standpoint of a variety of legal specialties, while highlighting the differences between JDR and ADR.